MILLENNIAL’S INVESTMENT DECISION IN CAPITAL MARKET INVESTMENT WITH FINANCIAL BEHAVIOR AS AN INTERVENING VARIABLE - Ramadani, Arienda Gitty; Tubastuvi, Naelati; Fitriati, Azmi; Widhiandono, Hengky (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study aims to analyze the influence of financial literacy, financial experience, financial self -efficacy and risk tolerance on investment decisions mediated by financial behavior. The population in this study were local individual investors in the Indonesian Capital Market. Sample selection in this study was carried out using purposive sampling techniques. The sample used in this study was 300 samples. The data analysis techniques used in this study are descriptive statistical analysis, instrument testing, classical assumption test, multiple linear regression analysis, model fit test, and hypothesis test. The results of the study show that financial literacy, financial experience and financial self-efficacy have a positive effect on financial behavior. Risk tolerance does not have a positive impact on financial behavior. Financial literacy, financial self-efficacy, risk tolerance and financial behavior positively influence investment decisions. Financial experience has no positive effect on investment decisions. Financial behavior has proven to be able to mediate the influence of financial literacy, finan cial experience and financial self- efficacy on investment decisions. Financial behavior has proven unable to mediate the effect of risk tolerance on investment decisions.